2019
DOI: 10.1371/journal.pone.0211679
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling reveals correlations between spermiogram parameters and the metabolites present in human spermatozoa and seminal plasma

Abstract: In 50% of all infertility cases, the male is subfertile or infertile, however, the underlying mechanisms are often unknown. Even when assisted reproductive procedures such as in vitro fertilization and intracytoplasmic sperm injection are performed, the causes of male factor infertility frequently remain elusive. Since the overall activity of cells is closely linked to their metabolic capacity, we analyzed a panel of 180 metabolites in human sperm and seminal plasma and elucidated their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 55 publications
8
62
0
3
Order By: Relevance
“…Several studies have already confirmed the relation between carnitines and sperm quality, linking the carnitine concentration in the seminal plasma to several sperm parameters 24‐29 and fertility 27,28,30 . More recently, metabolomic studies have confirmed a positive correlation between carnitine concentration in the seminal plasma and sperm concentration in the ejaculate 15,31 . By combining with carnitine, fatty acids form acylcarnitines, which allow their transport across the inner mitochondrial membrane to supply energy through beta‐oxidation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies have already confirmed the relation between carnitines and sperm quality, linking the carnitine concentration in the seminal plasma to several sperm parameters 24‐29 and fertility 27,28,30 . More recently, metabolomic studies have confirmed a positive correlation between carnitine concentration in the seminal plasma and sperm concentration in the ejaculate 15,31 . By combining with carnitine, fatty acids form acylcarnitines, which allow their transport across the inner mitochondrial membrane to supply energy through beta‐oxidation.…”
Section: Discussionmentioning
confidence: 90%
“…Spermine also has a role in sperm decapacitation, which allows the spermatozoa to perform its acrosomal reaction at the right time 46 . Spermine concentration in the seminal plasma has been positively correlated with sperm mobility, and negatively correlated with anomalies of the intermediate piece 15,31 . Furthermore, the spermine/spermidine ratio, which measures the activity of the spermine synthase, was significantly lower in the SOA group, indicating an impairment of the polyamine biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, researchers have determined different numbers of amino acids and peptides, in seminal plasma of bull, where glutamic and aspartic acid were the most abundant, and were associated with fertility and pregnancy rates (al-Hakim et al, 1970;Holden et al, 2017). Also, seminal plasma of human and other species were found to contain large numbers of amino acids (Engel et al, 2019;Santiago-Moreno et al, 2019). Fertility and sperm freezability are not always related.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids, biogenic amines, and lipids represent the majority of the sperm metabolome, and have been found to be related to conventional sperm parameters. In more detail, the nonessential amino acid glutamine (Gln), which has been reported to be the most abundant amino acid in both spermatozoa and seminal plasma, correlates significantly with sperm concentration and motility [44]. Arginine (Arg) was described as crucial for spermatogenesis and, as a consequence, Arg-deficient diets are associated with the presence of multinuclear giant cells in the testis and SPGF [45].…”
Section: Sperm Metabolomementioning
confidence: 99%